E-Commerce Online Buying and Selling Transactions in the Perspective of Islamic Law - Dedi Dedi (International Journal of Artificial Intelligence Research, 2022)
E-Commerce has created a new phenomenon in modern society's commercial dealings. Due to the novelty of the transaction model, the inheritance law of scholars has not yet been codified in any traditional fiqh text. In light of this fact, scholars must use ijtihad to discover Islamic law. The purpose of this study is to examine e-commerce online buying and selling transactions from an Islamic law standpoint. This study is a literature review using a standard legal research paradigm. It is a research model whose purpose is to establish the connection between legal structures and legal norms or principles. According to this study's findings about the deployment of online purchasing and selling, consumers chose to purchase things from the seller's website. The customer deposits multiple payments to the seller's account, and the seller provides the consumer the merchandise. The review of Islamic law pertaining to online purchasing and selling is permissible so long as there are no prohibited aspects in Islamic law that prohibit and clash with the idea of muamalah